216k views
0 votes
Which is the result when the equation y = − 2 5 x + 5 2 is converted to standard form?

User Steve HHH
by
5.7k points

2 Answers

5 votes

Answer:

-52 = -25x - y

Explanation:

y = -25x + 52

y - 52 = -25x

-52 = -25x - y

User Tomaz Canabrava
by
5.4k points
4 votes

Answer:

y + 25x =52

Explanation:

Ax + By = C is considered the standard form. Considering this we need to move x and y to the left and keep 52 in the right:

y = −25x + 52

We move -25x to the left

y + 25x = 52

I hope you find this information useful and interesting! Good luck!

User Csundman
by
6.2k points